Seleção de materiais com potencial aplicação na purificação de IgG humana - Gondim, Diego Romão (2017)
Immunoglobulins are proteins of the immune system, considered as antibodies of all animals, being responsible for the main mechanism of defense against foreign bodies (antigen). Therefore, the main objective of the present work was to purify the human immunoglobulins from isotype G (IgG) by ion exchange and affinity chromatography using different chromatographic matrix. To reach these objectives were synthesized Hydroxides, containing Mg/Al or Zn/Al and the CO32- anion; SBA 15 with and without zirconium heteroatom; and matrix based on chitosan modified with immobilized dyes (Reactive Red 120 - RV120 and Procion Red - MXR. HDL and SBA 15 are considered ion exchange chromatographic matrix whereas chitosan-based with dyes-ligand are pseudo-affinity matrix. The synthesized materials were characterized by X-Ray Diffraction (DR-X), Fourier Transform Infrared Spectroscopy (FTIR) and N2 Adsorption-Desorption Isotherm. Subsequently, fundamental batch data were obtained using solutions with Human Serum Albumin (HSA) and IgG, as well as solutions with diluted human serum in buffer. Zn/Al-LDH and SBA 15 (without zirconium) were the main ion exchange matrix, since they had a higher amount of IgG adsorbed, with values above 600 mg g-1. However, according to the SDS-PAGE electrophoresis analyzes, these materials were not able to purify human IgG, being best recommended for a pre-purification of this protein. In contrast, pseudo-affinity matrix showed selectivity for specific IgG domains, since SDS-PAGE electrophoresis analyzes showed that IgG was purified from binary mixtures and diluted human serum.